Electron emission in collisions of dressed ions with He atoms. (29th January 2015) - Fregenal, D; Monti, J M; Fiol, J; Bernardi, G; Suárez, S G; Fainstein, P D; Rivarola, R D; Schuch, R
Abstract: We present theoretical and experimental results for angular and energy distributions of electrons emitted in collisions of B 2+ with He atoms. In particular, we analyze the cusp formed by projectile Electron Loss to Continuum (ELC) and Electron Capture to Continuum (ECC). The cusp shape dependence on the electronic initial state is discussed and compared with our previous measurements on Li + + He. The projectile incident energy was about 414 keV/u and the electron detection angle was varied between 0° and 150°. The experimental data is compared with three-body quantum Continuum-Distorted-Wave calculations.